Anti-Malaria and Anti-Typhoid Effects of Cocus nucifera L Husk Extract - Okwara K. K; Mgbemena I. C; Emeka-Nwabunnia I; Nwoko M. C.; Nkwocha C. J. (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY (2536-6041), 2025)
The aim of the study is to evaluate the antimalaria and antityphoid effects of ethanolic extracts of Cocus nucifera husk. The ethanolic extracts were obtained by maceration of pulverized plant parts in ethanol for 48hours with continual agitation, extracts obtained were evaluated for acute toxicity test (LD50), phytochemical analysis. Antimalarial suppressive and curative test were carried out using (84) albino mice (weighing 20 – 23g) which were infected intraperitoneally with 0.2ml of 10fold dilution of 1 ml of infected blood from malaria infected mice. Packed cell volume (PCV) was measured for both suppressive and curative analysis, percentage parasitemia were also determined. Antimicrobial sensitivity test of the plant samples against Salmonella typhi were carried out. The acute toxicity test (LD50) caused no toxicity and death to mice after oral administration even at high doses of 5000 mg/kg of the plant extracts, phytochemical studies reveal the presence of flavonoids, terpenoids and more phenols in the plant extracts, also, proteins and tannins were observed in moderate level. The suppressive effect of the plant extract were statistically significant (p < 0.05) with coconut husk extract at 500mg/kg having the highest parasitemia suppression of 58.03%, while chloroquine 25mg/kg (40.05%) suppression. Chloroquine and extract treated groups increased the PCV of Plasmodium berghei infected mice when compared to control group, but were not statistically significant (p > 0.05). The curative effect of the Chloroquine treated group had a significant (p < 0.05) effect with increased PCV while the 250mg/kg and 500mg/kg C. nucifera husk extract treated group had a slight increase in their PCVs but it was not statistically significant (p > 0.05). Chloroquine statistically reduced the parasitemia load of P. berghei (p < 0.05), with percentage suppression of 81.25%, the coconut husk 250mg/kg and 500mg/kg treated groups had percentage suppression of 40.60% and 40.00% respectively which is statistically significant (p < 0.05). From the study, chloroquine produced the highest curative effect followed by the coconut husk extract. Ethanolic extract of coconut husk had better antibacterial effects on Salmonella typhi at 400mg/ml, 200mg/ml and 100mg/ml concentrations with zones of inhibition better than some control antibiotics like Ampicillin, Ceporex but similar with that of Streptomycin, Ofloxacin, Augmentin, Ciprofloxacin. Ethanolic extract of Cocos nucifera husk possesses antimalarial properties at doses of 250 mg/kg and 500 mg/kg. The C. nucifera ethanolic husk extract at 500 mg/kg had better prophylaxis effects and malaria parasite suppression than chloroquine but with a cure rate less than that of chloroquine but statistically significant at both dosages of 250 mg/kg and 500 mg/kg.